The Effect of Endurance Training Onincreased Vo2max in Athleteswomen's Ssc Volleyball - Susan Mersalina Anmama; A. Fenanlampir; Mieke Souisa (International Journal of Education, Information Technology, and Others, 2023)
The aim of this study was to determine whether there was an effect of endurance training on increasing VO2max in female SSC volleyball athletes. This research is experimental research, where the author wants to know the ability of female SSC (sport science club) volleyball athletes to increase endurance. The design of this research is One Group Pretest-Posttest. The research results showed that the effect of endurance training using fartlek training showed real effectiveness in the sense of the word reliable as an exercise to increase Vo2max in SSC (sprot science club) volleyball athletes.